(untitled) (Web of Teachers: Inderscience Research, 2025)
The study of nouns in both English and Russian languages unveils a rich tapestry of structural and semantic characteristics that elucidate the unique linguistic frameworks each language embodies. Nouns serve as fundamental building blocks within these languages, encapsulating not only objects and entities but also intricate notions of plurality, possession, and agency. English, with its relatively flexible noun structure, allows for the easy formation of compounds and the application of prefixes and suffixes, whereas Russian noun morphology is characterized by a more complex system of inflections and cases that dictate grammatical relationships. This comparative analysis raises pertinent questions about how these structural differences impact meaning and usage in everyday communication. By exploring the nuances of noun formation, semantics, and their contextual applications, this essay aims to foster a deeper understanding of the interconnections between linguistic structure and meaning, highlighting both the divergences and convergences between these two languages.